Temperature and Gate-Length Dependence of Subthreshold RF Detection in GaN HEMTs - Gaudencio Paz-Martínez; Ignacio Íñiguez-de-la-Torre; Héctor Sánchez-Martín; José Antonio Novoa-López; Virginie Hoel; Yvon Cordier; Javier Mateos; Tomás González (Sensors, 2022)
The responsivity of AlGaN/GaN high-electron mobility transistors (HEMTs) when operating as zero-bias RF detectors in the subthreshold regime exhibits different behaviors depending on the operating temperature and gate length of the transistors. We have characterized in temperature (8–400 K) the detection performance of HEMTs with different gate lengths (75–250 nm). The detection results at 1 GHz can be reproduced by a quasi-static model, which allows us to interpret them by inspection of the output <semantics>ID </semantics>−<semantics> VDS</semantics> curves of the transistors. We explain the different behaviors observed in terms of the presence or absence of a shift in the zero-current operating point originating from the existence of the gate-leakage current jointly with temperature effects related to the ionization of bulk traps.